Peripheral CD56+CD16+ NK Cell Populations in the Early Follicular Phase Are Associated With Successful Clinical Outcomes of Intravenous Immunoglobulin Treatment in Women With Repeated Implantation Failure - Ho, Yao-Kai; Chen, Hsiu-Hui; Huang, Chun-Chia; Lee, Chun-I; Lin, Pin-Yao; Lee, Maw-Sheng; Lee, Tsung-Hsien (Frontiers in Endocrinology, 2020)
The percentage of peripheral CD56+CD16+ NK cells in the early follicular phase on days 2-3 of the menstrual cycle in repeated implantation failure (RIF) patients was used to evaluate the impact of intravenous immunoglobulin (IVIG) on ART cycles. A total 283 patients with RIF consisting of at least 3 ART failures and at least 2 high quality embryo transfers were recruited. A logistic regression analysis for the peripheral immunological profile was completed to predict implantation success and compare the implantation and pregnancy rates between groups with ≤10.6% and >10.6% of CD56+CD16+ NK cells in the early follicular phase. The logistic regression and receiving operating curve analyses showed that patients with ≤10.6% of peripheral CD56+CD16+ NK cells in the early follicular phase showed a lower pregnancy rate within the RIF group without IVIG. Patients with peripheral CD56+CD16+ NK cells ≤10.6% and without IVIG treatment showed significantly lower implantation and pregnancy rates (12.3% and 30.3%, respectively) when compared with the CD56+CD16+ NK cells >10.6% group (24.9% and 48.0%, respectively, p<0.05). Furthermore, the patients with CD56+CD16+ NK cells ≤10.6% given IVIG starting before ET had significantly higher implantation, pregnancy and live birth rates (27.5%, 57.4% and 45.6%, respectively) when compared with the non-IVIG group (12.3%, 30.3% and 22.7%, respectively, p<0.05). Our results showed that a low percentage of peripheral CD56+CD16+ NK cells (≤10.6%) in the early follicular phase is a potential indicator of reduced pregnancy and implantation success rates in RIF patients, and IVIG treatment will likely benefit this patient subgroup.